انتهاكات الحقوق السياسية في اقليم كوردستان العراق (1991-2017) - محمود, أ.م.د. ريبوار كريم; كريم, م.م. نوزاد صالح (Sulaimani Journal for Humanities, 2023)
The research focused on the most important infringement of political human rights in the Kurdistan Region of Iraq. This issue has a great importance in human life. It is the right of every citizen to enjoy all his political rights, the governments and authorities must protect those rights and prevent harm and aggression to the human being. The research relied on a number of valuable sources in the field of political rights, all which contributed to providing us with information on the reality of political rights in the Kurdistan Region of Iraq, and how these rights were exposed to infringement in the period between (1991-2017). The study concluded with a number of conclusions, the most important of those are the decline in political rights in the Kurdistan Region, and the inability of the concerning governmental and non-governmental authority in the region to provide adequate guarantees to protect political rights, due to the slow performance of the government and the limited impact of the organizations’ work to achieve the best ways to guarantee the political rights. In addition, the lack of independence and weakness of the Parliament of the Kurdistan Region in performing its role in a highly effective manner, in addition to the decline in the role of the press and the media in monitoring the actions of the executive authority, and forming public opinion and raising its political level, which in turn constitutes pressure on the government to improve its policy for the better, all of that are still obstacles to protect political rights in the Kurdistan Region of Iraq.